Effect of storage conditions on quality and shelf life of selected winter vegetables (Journal of the Bangladesh Agricultural University, 2010)
Cabbage, cauliflower, country bean, tomato and pea were stored in room temperature for 8 days, at refrigerated (4°C) temperature for 12 days and at freezing temperature (-18°C) for 90 days. The vegetables were analyzed at every 2 days of storage period in room temperature, at the interval of 15 days at freezing and 3 days interval for refrigerated condition. Color, flavor, texture was better in freezing condition compared to the other conditions. The pH values after stored at room temperature 4.2, 4.32, 4.1, 3.33, 3.3, in refrigerated condition (without blanching) 4.83, 5.23, 3.33, 3.97, 4.37 and in refrigerated condition (with blanching) 3.27, 3.89, 3.98, 3.39, 4.77 and in freezing condition 5.47, 5.77, 4.76, 3.99 and 5.39 respectively. Vitamin C content of cabbage, cauliflower, country bean, tomato and pea after 8 days of storage at room temperature was 21.3 mg/100 g, 25.3 mg/100 g, 4.34 mg/100 g, 13.2 mg/100 g and 3.9 mg/100 g respectively. In refrigeration temperature (without blanching) after 12 days the values were 16.3 mg/100 g, 37.3 mg/100 g, 2.7 mg/100 g, 13.3 mg/100 g and 8.3 mg/100 g for cabbage, cauliflower, country bean, tomato and pea correspondingly. On the other hand in refrigeration condition (with blanching) vitamin C content of cabbage, cauliflower, country bean, tomato and pea were 3.3 mg/100 g, 18.3 mg/100 g, 2.4 mg/100 g, 2.9 mg/100 g and 9.3 mg/100 g in that order. Vitamin C content of cabbage, cauliflower, country bean, tomato and pea in freezing condition after 90 days of storage period were found 22.1 mg/100 g, 43.23 mg/100 g, 14.2 mg/100 g, 20.7 mg/100 g and 12.1 mg/100 g. The rate of weight loss increased with time progress of the storage period in all conditions. Keywords: Ambient temperature; Refrigeration; Freezing; Blanching; Cabbage; Cauliflower; Tomato; Country bean; Peas DOI: 10.3329/jbau.v6i2.4839 J. Bangladesh Agril. Univ. 6(2): 391-400, 2008